Facilitators and barriers of digital health technologies implementation in hospital settings in lower-income and middle-income countries since the COVID-19 pandemic: a scoping review protocol - Yew, Sheng Qian; Trivedi, Daksha; Adanan, Nurul Iman Hafizah; Chew, Boon How (BMJ Publishing Group, 2024)
Introduction The implementation of digital health technologies (DHTs) in hospitals worldwide has been uneven since the COVID-19 pandemic. Ambiguity in defining the landscape of DHTs adds to the complexity of this process. To address these challenges, this scoping review aims to identify the facilitators and barriers of implementing DHTs in hospitals in lower-income and middle-income countries (LMIC) since COVID-19, describe the DHTs that have been adopted in hospital settings in LMIC during this period, and develop a comprehensive classification framework to define the landscape of DHTs implemented in LMIC. Methods and analysis We will conduct a systematic search in PubMed, Scopus, Web of Science and grey literature. Descriptive statistics will be used to report the characteristics of included studies. The facilitators and barriers to DHTs implementation, gathered from both quantitative and qualitative data, will be synthesised using a parallel-results convergent synthesis design. A thematic analysis, employing an inductive approach, will be conducted to categorise these facilitators and barriers into coherent themes. Additionally, we will identify and categorise all available DHTs based on their equipment types and methods of operation to develop an innovative classification framework. Ethics and dissemination Formal ethical approval is not required, as primary data collection is not involved in this study. The findings will be disseminated through peer-reviewed publications, conference presentations and meetings with key stakeholders and partners in the field of digital health.